Effect of Azolla filiculoides meal inclusion in the napier silage total mixed ration on the in vitro cumulative gas production and digestibility - Rimi Hamidan, Mohammad Fitri; Mohd Nadzir, Mohd Noor Hisham; Abu Bakar, Muhammad Faisal; Shohaimi, Shamarina; Bidin, Habsah; Samat, Noraini (Universiti Putra Malaysia Press, 2022)
This study was carried out to determine the nutritional value and digestibility of total mixed ration (TMR) Napier silage with different Azolla filiculoides meal inclusion percentages. Samples of Azolla were cultivated in the tank with the media from 1.0 g/L dilution of sheep manure. Inclusion of 0% (control), 6% (T1), 10% (T2), 16% (T3), and 23% (T4) A. filiculoides meal was used to replace the proportion of Napier silage and soybean meal according to treatments with four replicates. All treatments were analyzed to determine the nutritional composition, and in vitro gas production was recorded for 96 h. In contrast, in vitro dry matter digestibility (IVDMD), in vitro organic matter digestibility (IVOMD), and metabolizable energy (ME) of each TMR mixture were determined using the published equation. As a result, only T4 had shown a significant difference (p <0.05) in crude protein (CP) and ether extract (EE) compared to other treatments. Values of dry matter (DM), CP, and ash of the TMRs were not affected on T1, T2, T3, and control. Neutral detergent fiber (NDF) and acid detergent fiber (ADF) were increased significantly at T3 and T4 compared to other treatments even though higher (p<0.05) acid detergent lignin (ADL) as replacement of 5.0% Napier silage and 1.0% soybean meal had shown a competitive value in their nutritional compared to the common TMR for ruminants. Therefore, a fermentation process was suggested to degrade indigestible components of A. filiculoides to enhance the potential of this species as an alternative feed source for a ruminant.